Efeito anti-inflamatório e antinociceptivo de proteínas isoladas do látex de Plumeria rubra L. em modelo experimental de artrite induzida por zymosan em camundongos - Pinheiro, Rachel Sindeaux Paiva (2017)
The Plumeria rubra is a laticifer plant of family Apocynaceae, popularly known as “Jasmim”. It is widely distributed in tropical and subtropical regions, including Brazil. Some studies show that the latex of P. rubra has gastric antiulcer effect,antioxidant and vasodilator activity. The aim of this study was to evaluate the effect of isolated proteins from Plumeria rubra latex (PrLP) in arthritis induced by zymosan (Zy). METHODOLOGY: This study was approved by the Ethics Committee on Animal Research of the UFC-CEPA (82/14). Arthritis was induced in female Swiss mice (n = 6) by injection of 0.1 mg Zy intra-articular. After 1 hour of Zy injecton, the animals were treated with saline or PrLP (12.5, 25, 50 and 100 mg/kg i.v.); the dexamethasone (2 mg/kg i.v.) was administered thirty minutes before Zy treatment. After six hours of arthritis induction, the animals were euthanized, the joint washing carried and collected for leukocyte count, determination of the myeloperoxidase (MPO) activity and inflammatory mediators (NO, TNF-α, IL-1β, IL-6 and IL-10). The edema was evaluated by measuring the diameter articular and the vascular permeability through extravasation evans blue. In addition, immunohistochemistry was performed for cyclooxygenase 2 (COX-2), NOSi, NfkB e TNF- α in the tissue.The mechanical hypernociception was induced by intra-articular injecton of Zy or intra-plantar injection of carrageenan or prostaglandin E2.The effect antinociceptive of PrLP was evaluated in the absence and in the presence of Naloxone (1 mg / kg; i.v.) and L-arginine (1g / kg; i.p.), which were administered 30 minutes before of the administration of PrLP. The statistical analysis were performed using the ANOVA/ Newman Keuls or Kruskal Wallis/Dunn post hoc test. Values of p <0.05 was considered statistically significant. RESULTS PrLP at doses of 25, 50 and 100 mg /kg iv reduced the leukocyte count (899.8 x 106 / ml ± 148; 1225 x 106 / ml ± 89.59 and 890 x 106 / ml ± 165.7, respectively), the neutrophil count (860.3 ± 97.57; 1108 ± 127.6 and 908.7 ± 159.9, respectively) and the MPO activity (12.1 ± 1.3;14.3 ± 0.6 and 8.9 ± 3.5 UMPO / ml, respectively). PrLP (25 mg/kg) modulated the concentrations of the inflammatory mediators such as NO, IL-1β, TNF-α and IL-6 (71.84 ± 9.1 mM;, 4569 ± 712.5;, 1409 ± 221.6 and 847.3 ± 260.4 pg/ml respectively) when compared to the saline group. PrLP (25 mg/kg). Reduced the edema, which significantly reduced joint diameter in the third (0.89 ± 0.001 mm) and in the sixth hour (0.99 ± 0.02 mm) and also reduced the extravasation of evans blue to the joint (40.46 ± 3.6 μg/g). In the tissue histopathological study, PrLP (25 mg / kg) significantly reduced the inflammatory infiltrate (with reduction in the neutrophil count), edema, synovial membrane involvement and haemorrhage. PrLP (25 mg / kg) was also able to reduces the immunohistochemistry labeling for COX-2, NOSi, TNF-α and NFkB. In mechanical hypernociception, PrLP (25 mg / kg) significantly reduced both the third (0.86 ± 1.3) and the sixth hour (1.08 ± 2.3), and this effect was reversed by the administration of L-arginine (1g / kg, ip) and naloxone (1mg / kg, iv). In addition, PrLP (25 mg / kg) significantly reduced carrageenin-induced plantar hypernociception in the third (1.74 ± 0.4) and fifth hour (1.5 ± 0.4) and prostaglandin-induced hypernociception in the third hour (1.4 ± 0.4). CONCLUSION: PrLP has antinociceptive and anti-inflammatory activity in the model of arthritis induced by Zy. The effect seems to be related to the decreased migration of neutrophils and the release of inflammatory mediators, reducing damage to the synovial membrane and hypernociception.